The Combination of Wheat Peptides and Fucoidan Protects Against Chronic Superficial Gastritis and Regulates Gut Microbiota: A Double-blinded, Placebo-controlled Study (P06-104-19) - Kan, Juntao (Curr Dev Nutr, 2019)
OBJECTIVES: Chronic gastritis is observed in almost half world population. Traditional medications against chronic gastritis might produce adverse effects, so alternative nutritional strategies are needed to prevent the aggravation of gastric mucosal damage. The aim of this study is to evaluate the protective effect of the combination of wheat peptides and fucoidan (WPF) on adults diagnosed with chronic superficial gastritis in a randomized, double-blind, placebo-controlled clinical trial. METHODS: Participants were randomized to receive WPF (N = 53) or placebo (N = 53) once daily for 45 days. The pathological grading of gastric mucosal damage was scored using gastroscopy. The fecal samples were collected for the determination of calprotectin, short-chain fatty acids (SCFA) levels and metagenomics analysis. The questionnaires for self-reported gastrointestinal discomforts, life quality and food frequency were collected throughout the study. RESULTS: WPF intervention reduced gastric mucosal damage of subjects (P < 0.001). Significantly less stomach pain (P < 0.001), belching (P = 0.028), bloating (P < 0.001), acid reflux (P < 0.001), loss of appetite (P = 0.021), increased food intake (P = 0.020), and promoted life quality (P = 0.014) were reported in the WPF group. WPF intervention significantly decreased fecal calprotectin level (P = 0.003) while slightly increased fecal SCFAs level (P = 0.092). Mechanistically, we found a shifted microbiota profile post-intervention with significantly increased bifidobacterium pseudocatenulatum (P = 0.032), eubacterium siraeum (P = 0.036), bacteroides intestinalis (P = 0.024) and decreased prevotella copri (P = 0.055). CONCLUSIONS: In conclusion, WPF intervention could be utilized as a nutritional alternative to reverse the progression of chronic gastritis. Furthermore, WPF played an important role in the regulation of gut microbiota and SCFA production, which might benefit the lower gastrointestinal tract. FUNDING SOURCES: Nutrilite Health Institute funded this research. SUPPORTING TABLES, IMAGES AND/OR GRAPHS: